(untitled) (Biocenosis, 2015)
This article provides a historical overview of how the expansion has occurred in the distribution of the coyote (Canis latrans), an opportunistic and generalist species that has been favored by undergone changes in their habitat, such as the reduction of their predators populations. This canine is stigmatized by humans as a predator of livestock and species of interest to hunters, so is being persecuted and hunted, without considering that plays important roles in the ecosystem. Some actions for control and management, and environmental awareness, may be important for the conservation of coyote and other wildlife species. Canid; Mammals; Expansion of distribution; Mexico